Using genetic tests for talent identification in sports: too soon to be true - Eynon, N.; Birk, R. (Journal of Pediatric Endocrinology and Metabolism, 2011)
In summary, genetic predisposition plays an important role in sports and exercise performance. Athletic performance is related to genetic background; however, to achieve outstanding achievements, it should be coupled with effective training programs and favorable lifestyle habits. The complete genetic profi le favoring elite athletic performance has not been completed, yet. Thus, the prediction of individual elite athlete performance on the basis of current knowledge in the fi eld is " too soon to be true " .